Dinuclear and Trinuclear Complexes of Copper(I) and Silver(I) Supported by a Highly Fluorinated Pyrazolate [3, 5‐(CF3)2Pz]– and N‐Heterocycles. Issue 31 (12th August 2019) - Dias, H. V. Rasika; Diyabalanage, Himashinie; Jayaratna, Naleen B.; Shaw, Daniel; Hettiarachchi, Champika V.; Parasar, Devaborniny
Abstract : The chemistry of trinuclear silver(I) and copper(I) pyrazolates with aromatic, bidentate N ‐heterocycles, 2, 2′‐bipyridine, 6, 6′‐dimethyl‐2, 2′‐bipyridine, 1, 10‐phenanthroline, 2, 9‐dimethyl‐1, 10‐phenanthroline, and 1, 8‐naphthyridine are presented. These N ‐donor ligands react readily with {[3, 5‐(CF3 )2 Pz]Ag}3 and {[3, 5‐(CF3 )2 Pz]Cu}3 providing mixed‐ligand complexes with all nitrogen coordination spheres at metal in high yield. The fluorinated pyrazolate acts as a bridging ligand in these complexes. The bipyridine and phenanthroline systems with donor lone pairs at an acute angle serve as bidentate chelators for copper and silver providing dinuclear complexes. They feature planar, boat or chair shaped Ag2 N4 or Cu2 N4 cores and four‐coordinate, tetrahedral metal sites. The 1, 8‐naphthyridine that has donor nitrogen lone pairs at a parallel orientation affords trinuclear copper and silver complexes with two‐ and three‐coordinate metal centers. It uses only one of its lone pairs effectively in these adducts for metal ion coordination. In addition, 1, 8‐naphthyridine moieties of these copper and silver complexes show intermolecular π–π stacking. Results presented here show the effects of donor nitrogen lone‐pair orientations of the bidentate N ‐heterocycles on the structures of the products resulting from their chemistry with {[3, 5‐(CF3 )2 Pz]Ag}3 and {[3, 5‐(CF3 )2 Pz]Cu}3 . Abstract : A range of silver and copper complexes featuring all nitrogen coordination environments have been isolated from the reactions between highly fluorinated silver(I) and copper(I) pyrazolates and aromatic, bidentate N ‐heterocycles.